Usages participatifs des technologies et désir d’émancipation : une articulation fragile et paradoxale - Serge Proulx (Communiquer)
Since the 1970s, the question of democratic participation has been tackled by communication scholars in both Europe and North America. We suggest some avenues of research for articulating the participative usage of digital technologies – considered simultaneously as facilitators for emancipation and for alienation – and, on the other hand, a set of individual and social practices aimed at the construction of a cognitive democracy. Or, in other words, the construction of a social and political regime in which people could have full rights to access knowledge, a right which tends to diminish with the gradual hyperspecialisation of disciplinary thinking in natural and social sciences. These emerging collaborative practices are aimed at the construction of “informational commons,” which are produced by epistemic communities offering resistance to the process of transforming information into a commodity, a central tenet of informational capitalism.